2018
DOI: 10.1371/journal.pgen.1007682
|View full text |Cite
|
Sign up to set email alerts
|

Single copy/knock-in models of ALS SOD1 in C. elegans suggest loss and gain of function have different contributions to cholinergic and glutamatergic neurodegeneration

Abstract: Mutations in Cu/Zn superoxide dismutase 1 (SOD1) lead to Amyotrophic Lateral Sclerosis (ALS), a neurodegenerative disease that disproportionately affects glutamatergic and cholinergic motor neurons. Previous work with SOD1 overexpression models supports a role for SOD1 toxic gain of function in ALS pathogenesis. However, the impact of SOD1 loss of function in ALS cannot be directly examined in overexpression models. In addition, overexpression may obscure the contribution of SOD1 loss of function in the degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 61 publications
3
52
0
Order By: Relevance
“…Thus, our data indicate a combination of gain- and loss-of-function phenotypes in sod H71Y /sod H71Y flies. Other groups have suggested that ALS caused by sod1 mutations is due to both gain and loss-of-function and our data generally support this model ( Baskoylu et al, 2018 ; Saccon et al, 2013 ; Sau et al, 2007 ).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our data indicate a combination of gain- and loss-of-function phenotypes in sod H71Y /sod H71Y flies. Other groups have suggested that ALS caused by sod1 mutations is due to both gain and loss-of-function and our data generally support this model ( Baskoylu et al, 2018 ; Saccon et al, 2013 ; Sau et al, 2007 ).…”
Section: Discussionsupporting
confidence: 89%
“…Notably, these same two mutations (G85R and G93R) were subsequently modeled as single-copy insertions, along with three other common SOD-1 mutations (A4V, H71Y, L84) in C. elegans . The impact on both glutamatergic and cholinergic neuron degeneration was examined for all five of these mutations ( Baskoylu et al, 2018 ). G93R displayed phenotypes consistent with a toxic gain-of-function phenotype in cholinergic neurons, while G85R caused glutamatergic neurodegeneration following exposure to the neurotoxin paraquat ( Baskoylu et al, 2018 ).…”
Section: Genetic Models Of Neurodegenerationmentioning
confidence: 99%
“…As another example, animals treated with quinolinic acid exhibited neurodegeneration due to glutamatergic neurotransmission defects ( da Silveira et al, 2018 ). Similarly, in single-copy knock-in SOD1 models of ALS, loss of sod-1 function produced defects in light touch response indicative of a disruption in glutamate signaling ( Baskoylu et al, 2018 ).…”
Section: Evaluation Of Neurobehaviormentioning
confidence: 99%
“…No overt defects were observed in any lines. To assess neurodegeneration, we used dye uptake assays, which provide a sensitive readout of glutamatergic neurodegeneration in other disease models (Baskoylu et al, 2018;Faber et al, 1999). In dye uptake assays, the intact sensory endings of specific glutamatergic sensory neurons take up fluorescent dyes from the environment and backfill cell bodies.…”
Section: Chimeric Hrp-1hslc D290v Causes Tdp-43 Ortholog-dependent Nementioning
confidence: 99%